Identitas Visual pada Signage System di Pusat Perbelanjaan Metro Indah Mall - Soedewi, Sri (Program Studi Desain Interior Unikom, 2019)
Mall is a modern shopping center that provides maximum comfort in shopping for visitors. Metro Indah Mall is the largest modern shopping center in East Bandung that provides a variety of needs. Inside Metro Indah Mall there are many facilities and a fairly large commercial area. To make mall visitors stay comfortable when exploring all areas and easily determine the location they want to visit, the visitors need an information board and wayfinding sign that easily to understand, attracts attention and has its own characteristics, soit will easily recognized and understood by visitors. This research uses a qualitative method by conducting observations, interviews, and distributing questionnaires to see how effectiveness the application of signage system are measured by visibility, readability, noticeability, readability, and the use of appropriate materials on signage. It is hoped that this research can help Metro Indah Mall in creating and implementing effective wayfinding sign, so it can improve visitors comfort and can improve the mall's image among visitors. Keywords: Mall, Effectiveness, Wayfinding sign.